Light and thermal excitation of depolarization current in indirect bandgap Alx Ga1-xAs - Scalvi, Luis Vicente de Andrade [UNESP]; Oliveira, L. [UNESP]; Siu Li, M. (My University, 1996)
Monochromatic light excitation in conjunction with thermally stimulated depolarization current measurements are applied to indirect bandgap AlxGa1-xAs. The obtained average activation energy for dipole relaxation is in very close agreement with the DX center binding energy. Monochromatic light induces state transition in the defect and makes possible the identification of dipoles observed in the dark. Charge relaxation currents are destroyed by photoionization of Al0.5Ga0.5As using either 647 nm Kr+ or 488 nm Ar+ laser lines, which are above the DX center threshold photoionization energy. It suggests that correlation may exist among charged donor states DX--d+. Sample resistance as a function of temperature is also measured in the dark and under illumination and shows the probable X valley effective mass state participation in the electron trapping. Ionization with energies of 0.8 eV and 1.24 eV leads to striking current peak shifts in the thermally stimulated depolarization bands. Since vacancies are present in this material, they may be responsible for the secondary band observed in the dark as well as participation in the light induced recombination process.